Characterization of hospitalized children who were victims of accidents with poisonous animals - Erica Costa Lima; Geraldo Rodrigo Alves Soares; Lucinéia de Pinho (Universidade Federal de Santa Maria, 2016)
Aim: To characterize the profile, the type of injury and care for children who were victims of venomous animals and admitted in a reference hospital in Montes Claros, Minas Gerais. Method: Retrospective study, from the examination of hospital records of children from birth to 10 years-old who were hospitalized between 2010 and 2013 because of unintentional injury caused by venomous animal. Data were analyzed using descriptive statistics. Results: We identified 75 cases of children who were victims of such accidents, most males over the age of five years-old and residents of urban areas. The injuries were mostly caused by scorpions and snakes. Hospitalization lasted on average three days. Final Considerations: This study highlights the need for systematic assistance to child victims of venomous animals, aside from staff training, especially for nurses, in ordem for them to care and drive actions to control these accidents.